Pengembangan Human Relation Perspektif Nilai-nilai al-Qur’an - Fauzi, Ahmad (Department of Qur'an dan Hadith Faculty of Ushuluddin and Philosophy UIN Sunan Ampel Surabaya, 2011)
Not least the manager (leader) who failed to carry out its duties and functions. This is largely due to the lack of attention to the human relations aspect in building a spirit of togetherness as one of the most dominant factor in the success of management. Since the beginning of its creation, mankind has been designed as a creature who can not live alone. Therefore, one man inevitably need to Communicate and Interact with other human beings. This study intends to examine the conceptual meaning of human relations and the urgency with psychological and sociological approach in the perspective of the values of the Koran, Because The Qur’anic principle is to guide human life. The shift in the orientation of this communication is Inseparable from the human relations that is increasingly widespread and seamless, everyone can relate to anyone who desired, Including Westerners and their world. The existence of two human relationships that must be Followed by two cultures is then led to the change tendency of the relations between the two models